A systematic review comparing Mytomicyn-C subtenon injection to sponge during trabeculectomy in open angle glaucoma: Oral Presentation - Observational Study - General practitioner - Ethelind, Rachel; Puspa, Prizka Avilia; Santoso, Wildan Iman (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesMitomycin-C (MMC) is an effective agent to prevent scarring during the healing process followingtrabeculectomy procedure by inhibiting the multiplication of cells producing scar tissue. The aim ofthis study is to compare the efficacy of Mitomycin-C (MMC) delivered by either subtenon injection orsponge application during trabeculectomy surgery in open angle glaucoma patients. MethodsA systematic search was done using several databases including Pubmed, Medline, Embase, Scopus,and Jstor. Inclusion criteria were open angle glaucoma patients underwent trabeculectomy surgery,given either MMC via subtenon or sponge application, article in English, Randomized ControlledTrial (RCT) studies which published in the last 10 years. Intra-Ocular Pressure (IOP), EndothelialCell Counts (ECC) and Bleb Morphologic features with at least 1 month follow-up were evaluated. ResultsTwo RCT studies were included in this study. Both studies demonstrated that sub-tenon injectionand sponge application has no significant difference regarding IOP reduction from the baseline.Regarding morphologic features, both studies favor subtenon to conventional sponge application.Lastly, ECC in both studies conclude that there was no marked differences. ConclusionThe outcome of administration of MMC through subtenon injection and sponge application werecomparable to one another. However, less vascularization are shown in subtenon injection group.